Welfare Spending and Quality of Growth in Developing Countries: A Note on Evidence from Hopefuls, Contenders and Best Performers - Simplice Asongu; Jacinta Nwachukwu (African Governance and Development Institute (AGDI), 2016)
The transition from the Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs) has shifted the policy debate from growth to `quality of growth' (QG). We explore a new dataset on QG by the IMF and classify 93 developing countries for the period 1990-2011 in terms of Hopefuls, Contenders and Best Performers. The aims are as follows: (i) to depict the contradiction between high-growth and poor social welfare and (ii) to assess the influence of education and health spending on the QG. We use quantile regressions to articulate least and best QG performers. Two key findings emerge. First, 31 of the 33 countries in the Hopefuls category are in SSA. Second, the effect of health is decreasingly positive from Hopefuls to Best Performers, while the impact of education is increasingly positive. As a main policy implication, it would benefit countries in SSA to invest more in health relative to education now, but decrease such health expenditure and increase education spending as the economies in the sub-region make the transition from Hopeful to Contenders and finally to Best Performers in terms of `quality of growth'.
Keywords: O40; O57; I10; I20; I32; 330; Quality of growth; Development; Education; Health